Investigating processes to support and improve informed financial consent in Australian cancer services: an implementation process mapping study and analysis - Natalie Taylor; Elizabeth Kennedy; Carolyn Mazariego; Raylene Cox; Kate Whittaker; Megan Varlow (BMJ Open)
Objectives Through implementation process mapping and thematic analysis, this study aimed to understand existing pathways of established informed financial consent (IFC) processes to develop general recommendations for implementing IFC in various cancer care settings.Design Implementation science-based process mapping qualitative study. The Consolidated Framework for Implementation Research (CFIR) informed the development of interview questions and a process map outlining a normative process or workflow for patient consults was used during the interviews.Setting Australian cancer care provider health services.Participants Australian healthcare professionals who provide services to cancer patients and indicated having an IFC process or activities in their service were approached through existing networks to participate in a semistructured interview.Results Ten healthcare professionals who regularly worked with cancer patients were interviewed. IFC processes varied by professional specialty (ie, general practice, surgery, radiation oncology and medical oncology) and healthcare settings (eg, public and private). An aggregated process map that highlights the key components of IFC processes discussed was created and includes strategies such as centralised points of contact, consolidated information delivery, reiteration of information by others or at various time-points and the use of follow-up appointments to revisit the financial impact of treatment. Interview themes identified barriers and facilitators such as training, resources and templates that to support or hinder IFC in accordance with CFIR domains.Conclusions The themes and aggregated process map provide timely recommendations for healthcare professionals who provide services to cancer patients to facilitate IFC with their patients prior to treatment or as treatment changes. These practical actions will assist healthcare professionals and services providing cancer care to integrate IFC practices and processes into their routine patient interactions. Further work should identify implementation strategies to integrate and scale-up these evidence-based IFC processes and practices across the healthcare system.